Duration of Humoral and Cellular Immunity 8 Years After Administration of Reduced Doses of the 17DD-Yellow Fever Vaccine - Costa-Rocha, Ismael Artur da; Campi-Azevedo, Ana Carolina; Peruhype-Magalhães, Vanessa; Coelho-dos-Reis, Jordana Grazziela; Fradico, Jordana Rodrigues Barbosa; Souza-Lopes, Thalles; Reis, Laise Rodrigues; Freire, Larissa Chaves; Costa-Pereira, Christiane; Mambrini, Juliana Vaz de Melo; Maia, Maria de Lourdes de Sousa; Lima, Sheila Maria Barbosa de; et al. (Frontiers in Immunology, 2019)
The present study aims to determine whether 17DD-YF-specific humoral and cellular immunological memory is maintained 8-years after primary vaccination with subdoses (10,447IU;3,013IU;587IU;158IU;31IU). Our results demonstrated that vaccinees, who had seroconverted following primary vaccination and had not been revaccinated, present similar neutralizing antibodies levels and YF-specific cellular memory, particularly CMCD4 and EMCD8 as compared to the reference full dose (27,476IU). Although, PRNT seropositivity rates were similar across subgroups (94%;82%;83%;94%;80% and 91%, correspondingly), only doses above 587IU elicited similar iterative proportion of seropositivity rates (89%;80%;80% and 91%, respectively) as compared to 158IU and 31IU (68% and 46%, respectively). Noteworthy were the strong positive correlations (“EMCD4,EMCD8” and “TNFCD8,IFNCD8”) observed in most subdoses, except for 31IU. Major similarities underscored the preserved antibody titers and the outstanding levels of EMCD8, relevant correlates of protection for YF-specific immunity. These findings provide evidences to support the regular use of dose sparing strategy for YF vaccine in adults.